(untitled) (Faridpur Medical College Journal, 2020)
The field of Radiology and Nuclear medicine has advanced from era of X-rays to today’s modern imaging techniques, most of which use the ionizing radiation. With the benefits of better diagnosis and treatment, it has caused manifold increase in radiation exposure to the patients and the radiology and nuclear medicine personnel. Many studies done till date have clearly documented the harmful effects of ionizing radiation from radiation exposure, especially cancer. This is more important in paediatric population as their tissues are more radiosensitive, and they have more years to live. Diagnostic and therapeutic radiological procedures including nuclear medicine are integral part of modern medical practices, exposing both patients and medical staff to ionizing radiation. Without proper protective measures, this radiation causes many negative health effects. Hence, proper knowledge and awareness regarding the radiation hazards and radiation protection is mandatory for health professionals, especially the nuclear medicine and radiology professionals. International Commission on Radiation Protection (ICRP) has recommended two basic principles of radiation protection, justification of the practice and optimization of protection. Faridpur Med. Coll. J. Jul 2019;14(2): 100-103